Storm Surge Response to Typhoon Tracks along the Korean Peninsula: Numerical Modeling Derived from Historical Typhoons - Kim, Hyeon-Jeong; Jin, Hoyeong; Min, Byung-Il; Lee, Woo-Dong (Han-guk haeyang gonghak hoeji (Online), 2025)
Storm surges induced by typhoons pose a significant threat to coastal regions, particularly in areas with complex shorelines and shallow waters. In this study, we investigated the impact of typhoon tracks on storm surges along the Korean Peninsula through numerical simulations based on synthetic typhoon scenarios derived from historical data. Specifically, the Advanced Circulation (ADCIRC) model was employed to simulate storm surges using scenarios based on six historical typhoons that followed common tracks into the West, South, and East seas of the Korean Peninsula. The results indicate that storm surge heights and volumes are significantly influenced not only by typhoon intensity but also by coastal morphology and landfall location. The west and south coasts, characterized by intricate bay structures, experienced amplified storm surge heights owing to water accumulation effects, whereas the east coast exhibited relatively low surge levels. The temporal evolution of storm surges further revealed that prolonged surge durations contribute to increased inundation risk. Additionally, storm surge heights varied notably when historical typhoons were simulated along different tracks, highlighting the importance of track uncertainty in storm surge forecasting. These findings emphasize the need for region-specific coastal disaster mitigation strategies, considering the combined effects of typhoon intensity, track, and coastal morphology.